Beyond Genocide: Transitional Justice and Gacaca Courts in Rwanda The Search for Truth, Justice and Reconciliation - Sullo, Pietro (International Criminal Justice Series,, 2018)
Combining both legal and empirical research, this book explores the statutory aspects and practice of gacaca courts (inkiko gacaca), the centrepiece of Rwanda's post-genocide transitional justice system, assessing their contribution to truth, justice and reconciliation. The volume expands the knowledge regarding these courts, assessing not only their performance in terms of formal justice and compliance with human rights standards, but also their actual modus operandi. Scholars and practitioners have progressively challenged the idea that genocide should be addressed exclusively through 'westernised' criminal law, arguing that the uniqueness of each genocidal setting requires specific context-sensitive solutions. Rwanda's experience with gacaca courts has emerged as a valuable opportunity for testing this approach, offering new home-grown solutions for dealing with the violence experienced in 1994 and beyond that were never previously tried. Due to their unique features, gacaca courts have attracted the attention of researchers from different disciplines and triggered dichotomous reactions and appraisals. Anchoring the assessment of gacaca courts in a comprehensive legal analysis in conjunction with field research, this book addresses the tensions existing within the literature. Through the direct observation of gacaca trials, interviews and informal talks with genocide survivors, defendants, ordinary Rwandans, academics and practitioners, a purely legalistic perspective is overcome, offering instead an innovative bottom-up approach to meta-legal concepts such as justice, fairness, truth and reconciliation. Outlining their strengths and shortcomings, this book highlights what aspects of gacaca courts can be useful in other post-genocide contexts, and provides crucial lessons learned in the realm of transitional justice. The book is primarily aimed at researchers working in, among others, the areas of international criminal law, genocide and transitional justice, while practitioners, students and others with a professional interest in the topics addressed may also find the issues raised relevant. Pietro Sullo teaches public international law and international diplomatic law at the Brussels School of International Studies of the University of Kent in Brussels. He is particularly interested in international law, human rights, transitional justice, international criminal law and refugee law.